The relationship between pathological internet use and psychiatric difficulties in adolescents during COVID-19 pandemic - Ayyıldız, Didem; Gümüştaş, Funda (The European Research Journal, 2023)
Objectives: Internet addiction has been attracting widespread interest due to the increase in screen time related to lectures, decrease in social activities and spending more time at home due to the education restriction all over the world. It was aimed to determine the psychiatric difficulties for before pandemic period and distance education period, separately and to evaluate the relationship between adolescents' pathological internet usage and difference in psychiatric difficulties. Methods: Four hundred thirty-eight adolescents aged 11-17 years, secondary and high school students were included in the study. An online survey was created consists of “Young Internet Addiction Test-brief form” (IAT), “Strengths and Difficulties Questionnaire” (SDQ) and researcher form using Google forms application. Youths completed the SDQ retrospectively for two separate time points: during the school restriction period and before the pandemic. Results: According to the results of our study, the number of changed areas (sleep, eating habits, leisure/social/physical activities) (B= 3.071, p < 0.001) and the change in SDQ-Peer relationship subscale score (B=1.193, p = 0.019) were among the factors significantly predict pathological internet use levels, respectively. Conclusions: Studies enable understanding the relationship between pathological internet usage and psychiatric difficulties would be useful for the organization of preventive interventions in case similar outbreaks occurred in the future.